THE IMPORTANCE OF DIETARY HYGIENE IN THE MANAGEMENT OF GASTROINTESTINAL DISEASES (International journal of medical sciences, 2025)
Gastrointestinal (GI) diseases represent a significant global health burden, and therapeutic diets are a cornerstone of their management. However, the efficacy of these diets is critically dependent on strict dietary hygiene, a factor that is often overlooked. Contamination of food with microbiological pathogens, allergens, or chemical irritants can not only trigger acute symptoms but also exacerbate chronic inflammatory conditions (e.g., IBD) and disrupt the delicate gut microbiome. This review synthesizes the evidence linking food hygiene practices—from sourcing and preparation to storage—to clinical outcomes in patients with GI disorders, highlighting a critical implementation gap in modern gastroenterological care.